INTERPERSONAL COMMUNICATION WITHIN THE ‘SATU SENYUM’ WHATSAPP COMMUNITY AMONG PARENTS OF CHILDREN WITH CLEFT LIP AND PALATE - Elysa Wahyuni; Tina Kartika (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
Cleft lip and palate (CLP) is a congenital condition that not only affects children physically but also creates emotional challenges for parents. In dealing with this situation, parents require both informational and emotional support from their social environment. One form of support emerges through digital communities such as the WhatsApp group “Satu Senyum,” which serves as a platform for parents of children with CLP to share experiences. This study aims to analyze interpersonal communication within the WhatsApp community “Satu Senyum.” The research employs a qualitative approach using content analysis of conversations among community members. The findings indicate that interpersonal communication in the community is characterized by openness in sharing experiences, empathy toward other members, supportive interactions through information exchange, positive attitudes in providing encouragement, and equality in communication among members. These findings suggest that the WhatsApp community functions as a communication space that fosters social support and strengthens relationships among parents of children with CLP.